Интенсивность внешнего воздушного потока как определяющий фактор формирования граничных условий теплообмена на поверхностях зданий - Маляренко, В. А.; Орлова, Н. О. (НТУ "ХПИ", 2016)
Розглянуто вплив зовнішнього повітряного потоку на граничні умови теплообміну. Визначаються характеристики в області гальмування і відриву повітряного потоку. На основі досліджень повітряного потоку в областях гальмування і відриву розглянуті основні чинники при визначенні теплопереносу на поверхні будівель.

The influence of the external air stream on the heat transfer boundary conditions. Identify the characteristics of braking and the separation of air flow. Based on research in the areas of air flow separation and braking are considered key factors in determining the heat transfer on the surface buildings.
Intensity of the external air stream as a determining factor in the formation of the heat exchange boundary conditions on surface buildings
Keywords: обтекание; скорость ветра; торможение; отрывное течение; пограничный слой; ПС; приземной слой